Optimizing Vocational School Revenue through Regional Public Service Agency Implementation: The Principal’s Strategic Role - Arin Ika Puspitaningsih; Elis Dwi Wulandari; Nurul Faizah; Ömer Şaban; Mernawati Mernawati (Institut Agama Islam Negeri (IAIN) Bone, 2026)
This study examines the principal’s leadership role in formulating strategies to increase Regional Public Service Agency (RPSA) revenue in Vocational High Schools. Employing a descriptive qualitative approach at SMKN 2 Banjarbaru, South Kalimantan, Indonesia, data were gathered through observation, interviews, and documentation. The analysis followed a framework of data collection, data condensation, data display, and drawing/verification, facilitated by NVivo software. The findings show the principal primarily acts as a manager driving strategic initiatives to optimize revenue generation. These initiatives include strategic planning, corporate partnerships, human resources empowerment, and product and service innovation. These strategies improved financial outcomes, with the 2024 RPSA budget realization exceeding the target by 16.6%. Furthermore, transparent and accountable financial management, supported by systematic monitoring and evaluation, reinforces institutional trust and sustainability. Practically, this study highlights the importance of integrating instructional, managerial, and entrepreneurial (hybrid) leadership to optimize financial autonomy and sustain revenue generation in vocational schools. Penelitian ini mengkaji peran kepemimpinan kepala sekolah dalam merumuskan strategi peningkatan pendapatan Badan layanan Umum Daerah (BLUD) pada Sekolah Menengah Kejuruan (SMK). Menggunakan pendekatan kualitatif deskriptif di SMKN 2 Banjarbaru, Kalimantan Selatan, Indonesia, data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Analisis dilakukan menggunakan kerangka pengumpulan data, kondensasi data, penyajian data, serta penarikan/verifikasi kesimpulan, dengan bantuan perangkat lunak NVivo. Hasil penelitian menunjukkan bahwa kepala sekolah terutama berperan sebagai manajer yang mendorong inisiatif strategis untuk mengoptimalkan peningkatan pendapatan. Inisiatif tersebut meliputi perencanaan strategis, kemitraan dengan dunia usaha/industri, pemberdayaan sumber daya manusia, serta inovasi produk dan layanan. Strategi ini meningkatkan kinerja keuangan, yang ditunjukkan oleh realisasi anggaran BLUD tahun 2024 yang melampaui target sebesar 16.6%. Selain itu, pengelolaan keuangan yang transparan dan akuntabel, yang didukung oleh monitoring dan evaluasi secara sistematis, memperkuat kepercayaan serta keberlanjutan institusi. Secara praktis, penelitian ini menegaskan pentingnya integrasi kepemimpinan manajerial dan kewirausahaan dalam mengoptimalkan otonomi keuangan serta menjaga keberlanjutan pendapatan di sekolah menengah kejuruan.